Changes in cognition, coping, pain and emotions after 12-months access to the digital self-management program EPIO - Strand, Elin Bolle; Varsi, Cecilie; Børøsund, Elin; Eide, Hilde; Schreurs, Karlein M. G.; Waxenberg, Lori B.; Weiss, Karen E.; Morrison, Eleshia J.; Støle, Hanne Stavenes; Kristjansdottir, Ólöf Birna; Stubhaug, Audun; Solberg Nes, Lise (Frontiers in Psychology, 2025)
BackgroundPsychosocial pain self-management interventions can be of support for people living with chronic pain. Since psychosocial support is not always accessible, digital health interventions may increase outreach of these types of evidence-based interventions.ObjectivesTo explore participants' experiences from 12-month access to the digital pain self-management program EPIO, particularly in terms of any behavioral and/or psychological changes experienced.MethodsParticipants (N = 25) engaged in individual semi-structured interviews following 12-month access to the EPIO intervention. Qualitative thematic analyses were conducted seeking to identify any behavioral and/or psychological changes experienced through intervention use, and what contributed to these changes.ResultsParticipants were predominantly women (72%), median age 46 (range 26–70), with a range of self-reported pain conditions and the majority reporting pain duration >10 years (64%). Analyses identified three main themes and subsequent sub-themes: (1) Changes in Cognition; insight and self-awareness, acceptance and shifting focus, (2) Changes in Coping; pain, emotions, and activity pacing, and (3) Content and Functionality Specific Engagement; breathing and other mind-body exercises, thought-reflection exercises, and functionalities.ConclusionsPeople with chronic pain experienced positive behavioral and/or psychological changes in terms of cognition and coping after 12 months access to the EPIO digital pain self-management program. The most prominent changes included increased understanding of the connection between own thoughts, feelings, and behavior, gaining concrete strategies to cope with everyday life living with pain, and utilizing these strategies to reduce pain and interference of pain, as well as to improve emotion regulation and psychological wellbeing.